1981
DOI: 10.1029/jb086ib10p09397
|View full text |Cite
|
Sign up to set email alerts
|

Radon content of groundwater as an earthquake precursor: Evaluation of worldwide data and physical basis

Abstract: Abstract. The properties of a worldwide data set of 91 radon (222Rn) anomalies (the frequency of occurrence, the precursor time interval, and the distribution of peak amplitudes) are correlated with earthquake data such as the respective magnitude and epicentral distance. These anomalies were reported as precursors to earthquakes in the United States,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(105 citation statements)
references
References 25 publications
4
97
0
1
Order By: Relevance
“…However, this simplified picture is frequently contradicted by the lack of significant anomalies recorded before an earthquake (Kerr, 1978;King, 1981;Tsunogai and Wakita, 1995;Steinitz et al, 2003). Moreover, negative anomalies are sometimes measured at the seismic source (Hauksson, 1981;Kuo et al, 2006), while contemporaneous positive anomalies are inexplicably recorded at monitoring stations located hundreds of kilometres away (Kerr, 1978(Kerr, , 1981. Alternating increases and decreases of radon emissions are also measured prior to earthquakes (Wakita et al, 1980;Igarashi et al, 1995).…”
Section: Introductionmentioning
confidence: 96%
“…However, this simplified picture is frequently contradicted by the lack of significant anomalies recorded before an earthquake (Kerr, 1978;King, 1981;Tsunogai and Wakita, 1995;Steinitz et al, 2003). Moreover, negative anomalies are sometimes measured at the seismic source (Hauksson, 1981;Kuo et al, 2006), while contemporaneous positive anomalies are inexplicably recorded at monitoring stations located hundreds of kilometres away (Kerr, 1978(Kerr, , 1981. Alternating increases and decreases of radon emissions are also measured prior to earthquakes (Wakita et al, 1980;Igarashi et al, 1995).…”
Section: Introductionmentioning
confidence: 96%
“…Several investigators have proposed that micro-fracturing prior to major seismic events is responsible for precursory increases in ion and gas concentrations PAGEOPH, (HAUKSSON, 1981a;WAKITA, 1982;CAleta/., 1984;SuGISAKI eta/., 1983;. The exposure of fresh silicate surfaces, resulting from mineral fracture, is believed to both increase the rate of alteration reactions with groundwater and to allow the escape of trapped gases from the rock matrix.…”
Section: Increased Reactive Surface Area Modelmentioning
confidence: 99%
“…Recent monitoring programs have typically employed intermittent sampling from natural springs, shallow groundwater wells, or deep (2000m) monitoring wells, and have determined radon concentrations using gas-phase scintillation counting or liquid/liquid extraction of radon and liquid scintillation counting (FRIEDMANN and HERNEGGER, 1978;TALWANI et a/., 1980;TENG, 1980TENG, , 1984WAKITA et a/., 1980aWAKITA et a/., , 1985HAUKSSON, 1981a;HAUKSSON and GODDARD, 1981;ALLEGRI et a/., 1983;CHUNG, 1985;FRIEDMANN, 1985;KING, 1985aKING, , 1986LIV eta/., 1985;SHAPIRO eta/., 1985;SANTOYO et a/., 1987). Continuous monitoring of radon activities is now becoming a more accepted method, as the earlier results have shown that radon anomalies are frequently of short duration.…”
Section: Dissolved Gas Precursorsmentioning
confidence: 99%
“…In the past, substantive evidence in support of many diverse kinds of precursors, including hydrological and chemical changes in subsurface fluids prior to or at the same time as a large earthquake, has been found. Among these are valuable, insightful precursory changes in gases involved in both hydrothermal processes, like Rn, He, CO 2 , CH 4 , H 2 , Ar and N 2 , and in water chemistry, like Cl − , F − , NO 3 − and SO 4 2− (Hauksson 1981;King 1986;Tsunogai andWakita 1995, 1996;Sugisaki et al 1996;Toutain et al 1997;Chyi et al 2005;Italiano et al 2005;Ramirez-Guzman et al 2005;Walia et al 2005;. Such geochemical anomalies are generally associated with changes in a subsurface water circulating system in the process of earthquake generation (Thomas 1988;Rojstaczer and Wolf 1992;Muir-Wood and King 1993;Rojstaczer et al 1995;Sugisaki et al 1996).…”
Section: Introductionmentioning
confidence: 99%